Capturing High‐Resolution Air Pollution Features Using the Multi‐Scale Infrastructure for Chemistry and Aerosols Version 0 (MUSCIAv0) Global Modeling System. Issue 7 (28th March 2023) - Tang, Wenfu; Pfister, Gabriele G.; Kumar, Rajesh; Barth, Mary; Edwards, David P.; Emmons, Louisa K.; Tilmes, Simone
Abstract: The Multi‐Scale Infrastructure for Chemistry and Aerosols (MUSICA) enables the study of atmospheric chemistry and aerosols at global to local scales. MUSICA version 0 (MUSICAv0) is a configuration of the Community Earth System Model (CESM) with regional refinement (RR). We compared the regional scale spatial and temporal variabilities of air pollutants simulated by this newly developed multiscale model and a widely used regional model—WRF‐Chem (the Weather Research and Forecasting model coupled with Chemistry). The O3 and PM2.5 mean biases of the two WRF‐Chem simulations over the U.S. are 5–9 ppb and −3 μg/m 3 during August and September 2020. The MUSICAv0 simulation has larger O3 mean bias (11 ppb) but smaller PM2.5 mean bias (−1 μg/m 3 ) compared to the two WRF‐Chem simulations. As indicated by spatial and temporal statistical measures, the variability in meteorological parameters (temperature, precipitation), and ozone and PM2.5 are similar across a range of temporal and spatial scales in MUSICAv0 and WRF‐Chem. We demonstrate the new capability of the global MUSICAv0 at regional scale through two examples—(a) plumes from western U.S. fires that passed through the domain boundary of WRF‐Chem and were transported back into the domain and impacted air quality on the eastern U.S.; and (b) impact of stratospheric intrusion on the troposphere. Plain Language Summary: Atmospheric chemistry is impacted by many scales from local to global, and it also interacts with other components of the Earth system. However, previously models with different infrastructures have been used separately when dealing with different scales. Recently, unified multiscale models have been developed to allow representation of global to regional to local scales. The Multi‐Scale Infrastructure for Chemistry and Aerosols (MUSICA) is an example that enables chemistry and aerosols studies at all relevant scales. To demonstrate the value of MUSICA at regional scale, we compared MUSICA with a widely used regional model and found that MUSICA exhibits skills similar to the regional model in capturing regional scale features. In addition, we show the value of MUSICAv0 at regional scale as a global and multiscale model and unified infrastructure through two examples—transdomain‐boundary transport of fire plume and stratospheric intrusion to the troposphere. Key Points: The spatial and temporal variabilities of air pollutants simulated by Multi‐Scale Infrastructure for Chemistry and Aerosol version 0 (MUSICAv0) and Weather Research and Forecasting model coupled with Chemistry at regional scale are comparable MUSICAv0 with variable resolution provides consistent chemistry for plumes, such as from fires, leaving and reentering a regional domain The MUSICAv0 capability of simulating regional scales within the global context is further demonstrated by a stratospheric intrusion event